Fever in the returning traveller - Beeching, Nick (Medicine (Abingdon), 2005)
Fever is a common reason for acute hospital admission for tropical illness in UK referral units. A sensible working diagnosis can usually be formulated from a careful history and examination and initial simple investigations. The history should include details of exactly where the patient has been, what conditions he or she was living in, and the exact dates of arrival and departure. The quality of pre-travel advice and vaccinations, adherence to chemoprophylaxis against malaria, avoidance of insect bites and general behaviour abroad (including sexual history) are also important. Localizing features of the illness should be sought on examination. Maintain a high index of suspicion for underlying HIV. The most important illness to consider and exclude is malaria (about 40% of cases), and most of the remainder have cosmopolitan viral infections or imported infections such as an arbovirus (dengue), enteric fever or viral hepatitis. Rarer causes are usually evident from the history and examination, which presupposes a good knowledge of geographical medicine. Initial investigations should include adequate malaria films (supplemented by quick antigen detection tests in many laboratories) and blood count, repeated as necessary, blood, urine and faecal cultures, serum biochemistry, chest radiography and other imaging (e.g. liver ultrasonography) as indicated. In patients in whom malaria is suspected despite negative films, the combination of thrombocytopenia and splenomegaly is supportive but not diagnostic of malaria.